Aerosol delivered irradiated Escherichia coli confers serotype-independent protection and prevents colibacillosis in young chickens. Issue 7 (10th February 2023) - Paudel, Surya; Hess, Claudia; Kamal Abdelhamid, Mohamed; Lyrakis, Manolis; Wijewardana, Viskam; Thiga Kangethe, Richard; Cattoli, Giovanni; Hess, Michael
Highlights: Killed but metabolically active Escherichia coli were prepared by gamma irradiation. Irradiated E. coli showed broad protection against APEC challenges in young chickens. Aerosol application elicited superior protection compared with oculonasal route. Different strains showed varied level of protection, thus strain selection is crucial. A proof-of-concept of an irradiated vaccine against colibacillosis is established. Abstract: Escherichia coli causes colibacillosis in chickens, which has severe economic and public health consequences. For the first time, we investigated the efficacy of gamma-irradiated E. coli to prevent colibacillosis in chickens considering different strains and application routes. Electron microscopy, alamarBlue assay and matrix assisted laser desorption/ionization time-of- flight mass spectrometry showed that the cellular structure, metabolic activity and protein profiles of irradiated and non-treated E. coli PA14/17480/5-ovary (serotype O1:K1) were similar. Subsequently, three animal trials were performed using the irradiated E. coli and clinical signs, pathological lesions and bacterial colonization in systemic organs were assessed. In the first animal trial, the irradiated E. coli PA14/17480/5-ovary administered at 7 and 21 days of age via aerosol and oculonasal routes, respectively, prevented the occurrence of lesions and systemic bacterial spread after homologous challenge, as efficient as live infection or formalin-killed cells. In the second trial, a single aerosol application of the same irradiated strain in one-day old chickens was efficacious against challenges with a homologous or a heterologous strain (undefined serotype). The aerosol application elicited better protection as compared to oculonasal route. Finally, in the third trial, efficacy against E. coli PA15/19103–3 (serotype O78:K80) was shown. Additionally, previous results of homologous protection were reconfirmed. The irradiated PA15/19103–3 strain, which also showed lower metabolic activity, was less preferred even for the homologous protection, underlining the importance of the vaccine strain. In all the trials, the irradiated E. coli did not provoke antibody response indicating the importance of innate or cell mediated immunity for protection. In conclusion, this proof-of-concept study showed that the non-adjuvanted single aerosol application of irradiated "killed but metabolically active" E. coli provided promising results to prevent colibacillosis in chickens at an early stage of life. The findings open new avenues for vaccine production with E. coli in chickens using irradiation technology.